Quality evaluation of biscuits produced from wheat flour using peanut butter as fat substitute (Agriculture, Food, and Natural Resources Journal, 2025)
Quality evaluation of biscuits produced from wheat flour using peanut butter as a fat substitute was studied. Five samples were produced using 100% wheat flour (BBZ: 100% butter; RMD: 10% butter and 90% peanut butter; OKW: 20% butter and 80% peanut butter; BFB: 30% butter and 70% peanut butter; FMB: 40% butter and 60% peanut butter) and were subjected to different analyses: mineral, proximate, and vitamin composition, as well as sensory evaluation. The data obtained were statistically analyzed using ANOVA and mean separated by the Duncan Multiple Range Test (p
Keywords: Biscuits; Mineral; Peanut butter; Proximate; Wheat